Effect of chelating agents on alcohol dehydrogenase, a zinc containing enzyme - Gutierres, Catarina Alexandra Magro (2021)
Trabalho Final de Mestrado Integrado, Ciências Farmacêuticas, Universidade de Lisboa, Faculdade de Farmácia, 2019